The Effect of Lecturers Teaching Performance on Students Satisfaction in a University - Fajriani Azis; Muhammad Azis; M. Yusuf A. Ngampo; Abd Rijal (Universitas Negeri Makassar, 2021)
Student learning satisfaction is one of the indicators of teachers or lecturers success in teaching performance. It is assumed that the greater student satisfaction with a lecturer’s teaching style equates to better teaching performance by the lecturer. Current research has established that students satisfaction level within a university learning environment correlates with the lecturers teaching performance. The present study took place within a university examining students and lecturers in the Faculty of Economics at Makassar State University in Indonesia. The sample comprised 81 individuals who were investigated using a correlational descriptive study model. Data were gathered through questionnaires and the study of documents and then further analysed using a regression model that consisted of R2, F, t, and determination tests. Findings were that a lecturer’s performance, which involves preparation, opening, core, and closing activities in a lesson, positively and significantly correlated with student satisfaction levels.